Impact of diabetes on clinical outcomes after revascularization with sirolimus‐eluting and biolimus‐eluting stents with biodegradable polymer from the SORT OUT VII trial. Issue 4 (23rd September 2018) - Ellert, Julia; Christiansen, Evald Høj; Maeng, Michael; Raungaard, Bent; Jensen, Svend Eggert; Kristensen, Steen Dalby; Veien, Karsten Tange; Junker, Anders Bo; Jakobsen, Lars; Aarøe, Jens; Terkelsen, Christian Juhl; Kahlert, Johnny; et al.
Abstract: Objectives: In this substudy of the SORT OUT VII trial, the clinical outcomes among patient with diabetes mellitus treated with Orsiro sirolimus‐eluting stent (O‐SES; Biotronik, Bülach, Switzerland) or Nobori biolimus‐eluting stent (N‐BES; Terumo, Tokyo, Japan) were compared. Background: Diabetes is associated with increased risk of target lesion failure (TLF) after percutaneous coronary intervention. Methods: In total, 2525 patients were randomized to stent implantation with O‐SES ( n = 1261, diabetes: n = 236) or N‐BES ( n = 1264, diabetes: n = 235). The primary endpoint, TLF, was a composite of cardiac death, target‐lesion myocardial infarction (MI), or target lesion revascularization (TLR) within 2 years. Results: At 2 year, TLF did not differ between O‐SES vs N‐BES in diabetic (9.3% vs 9.4%; RR 0.98, 95% CI 0.54–1.78) patients. The individual components of the primary endpoint did not differ among stent type. In diabetics, cardiac death occurred in 3% of O‐SES‐treated and in 3.8% of N‐BES‐treated patients (RR 0.77, 95% CI 0.29–2.08), MI occurred in 3.0% of O‐SES‐treated and in 3.8% of N‐BES‐treated patients (RR 0.76, 95% CI 0.28–2.06) and TLR occurred in 5, 5% of O‐SES‐treated and in 6.0% of N‐BES‐treated patients (RR 0.91, 95% CI 0.43–1.95). Conclusion: TLF did not differ between O‐SES‐ and N‐BES‐treated diabetic patients.